Thermogravimetry (TG) applied to the study of the reaction of mercury with platinum-rhodium alloy - Ionashiro, E. Y.; Fertonani, F. L. (Elsevier B.V., 2002)
Thermogravimetry (TG) energy dispersive X-ray microanalysis (EDX), scanning electron microscopy (SEM), mapping surface, X-ray diffraction (XRD), inductively coupled plasma emission spectroscopy and atomic spectroscopy with cold vapor generation have been used to study the reaction of mercury with platinum-rhodium (Pt-Rh) alloy. The results suggest that, the electrodeposited Hg film reacts with Pt-Rh to form intermetallic compounds of different stability, when heated indicated by at least four weight loss steps. Intermetallic compounds as PtHg4 and PtHg2 was characterized by XRD. These intermetallic compound are the main product presents on the surface of the samples after remotion of the bulk mercury via thermal desorption techniques. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: alloy; rhodium; mercury; XRD; intermetallic